Anisotropic Deformation Mechanism in the Twin-Tube Tunnel Sections: Empirical Insight from Multi-Point Displacement Monitoring - Khelalfa, Houssam; Tekkouk, Mustapha; Boumehraz, Mohammed-Amin (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
This study evaluates the stability of a twin-tube tunnel through a combined approach of rock mass classification, numerical modeling, and real-time deformation monitoring. The rock mass along the tunnel alignment was characterized using the Rock Mass Rating (RMR) system, incorporating physical, geological, and geotechnical data from the project site. Support systems were designed for each geotechnical unit based on RMR and the Q-system support chart. Field monitoring was conducted over one year using a Leica TS09 tachometer and 3D displacement monitoring targets installed at the top heading and invert/bench, with data processed via Amberg Tunnel 2.0 software. Complementing the field measurements, 2D numerical analyses were performed to assess the left portal slope stability (Slide 6.0 software) and provisional support behavior (Phase2 2D program). The numerical results were validated against in-situ monitoring data, demonstrating strong agreement. The study confirms effective rock mass deformation control and satisfactory confinement stability, highlighting the reliability of the integrated methodology for tunnel stability assessment.